Desain Instrument Higher Order Thingking Pada Mata Kuliah Dasar-Dasar Matematika Di Jurusan PGSD - Ary Kiswanto Kenedi (AR-RIAYAH : Jurnal Pendidikan Dasar, 2018)
This research is motivated by the absence of standard instruments that can measure the ability of HOTS PGSD students. The type of research conducted is research development (development research) by using the ADDIE model (Analysis, Desagin, Development, Implementation, Evaluation). This research was conducted in class 17 BB 05 PGSD UNP. The research instrument used observation sheet and questionnaire. The result of this research is stated that HOTS instrument is worth dugunakan by expert of mathematician and expert of Indonesian language